Dedication and blessing of holy places - SAJ, MAREK (Prawo Kanoniczne, 2012)
The holy places have specific meaning in the life of the faithful. By the special liturgical act they are excluded from secular usage and intended to divine worship or to the burial of the faithful. Cannon Law gives us specific norms considering some holy places as: churches, chapels, altars, cemeteries. In order to become a holy place, this place must be dedicated or blessed. Church law states as well which form to choose: dedication or blessing. It says also about a person who can perform this rite. Important think in this case is choosing the day of dedication or blessing. The Code of Canon Law skips this theme however it is present in liturgical books. Knowledge this norms, which have been discussed in this article seems to be important, especially for the clergy, because the opinions presented by them are often contrary to the church’s regulations.